An Experimental Study on Drying of Green Apples - Doymaz, Ibrahim (TAYLOR & FRANCIS INC, 2009)
Drying behavior of green apples in a laboratory dryer was examined. Prior to drying, the apples were cut in 8mm thick slices, which were then treated with citric acid solution and blanched hot water at 80C. Next, they were dried at 65C with an air velocity of 2.0m/s. The shortest drying time (270min) was obtained with apples pretreated with citric acid solution. The drying data were fitted with 11 mathematical models available in the literature. Selection of the best model was investigated by comparing the determination of coefficient (R2), reduced chi-square (2), root means square error (RMSE), and mean relative percentage error (P) between the experimental and predicted values. The results showed that the Wang and Singh, logarithmic, and Verma et al. models gave the best results in describing thin-layer drying of apple slices. The effective moisture diffusivity of pretreated samples with citric acid solution was higher than the other samples.
Keywords: Blanching; Drying; Green apple; Mathematical modeling; Pretreatment solution; Rehydration rate; KINETICS; PRETREATMENTS; MODEL; TEMPERATURE; SUN; Engineering